Chondrosarcoma: A Diagnostic Imager's Guide to Decision Making and Patient Management - Logie, Chika I.; Walker, Eric A.; Forsberg, Jonathan A.; Potter, Benjamin K.; Murphey, Mark D. (Seminars in Musculoskeletal Radiology, 2013)
Chondrosarcoma is the third most common primary malignant bone tumor. Currently, outcomes are based largely on a histologic grading scale described by the World Health Organization (WHO) Classification of Bone Tumors (2002). This classification scheme possesses evident utility in the evaluation and management of higher grade tumors, but it is often unable to distinguish enchondromas from low-grade chondrosarcomas. This is problematic when low-grade lesions that are histologically similar to enchondromas demonstrate aggressive imaging features. Because histologic classification alone often belies the clinical significance of chondroid lesions, it is also important to consider radiologic staging as part of the clinical decision making process. This article focuses on medical decision support considerations relevant when confronted with this challenging subset of chondroid tumors, particularly differentiating the benign enchondroma from its notorious relative, the low-grade chondrosarcoma. In doing so, we present a review of the salient imaging features and discuss key differentiating characteristics.
Keywords: enchondroma; chondrosarcoma; chondroid tumors; cartilage tumors; histologic grading; radiologic staging